University of California Replacement of Cesium Irradiators with Alternative Technologies. Issue 2 (February 2020) - MacKenzie, Carolyn; Iwamoto, Keisuke S.; Smith, Kenneth
Abstract : Abstract: The University of California possesses a large number of 137 Cs irradiators that are used in a wide variety of medical and research applications. The university president made a system-wide decision to reduce the potential threat of malevolent use of 137 Cs by switching wherever feasible to x-ray irradiators over a 3-y period of time. A Radioactive Source Replacement Working Group of involved faculty was formed to study the topic and to make recommendations as to when alternative technologies could offer equivalency. The Working Group concluded that x-ray irradiators could replace 137 Cs irradiators in most applications, with some likely exceptions. They found that the depth dose curve for the 320 kVp x-ray irradiator was found to be nearly identical to that of 137 Cs down to a depth in tissue of 4 cm. It was concluded that x rays (energies ⩽320 keV) are more biologically effective than 137 Cs gamma rays, suggesting that lower doses of x rays will be required to achieve the same biological endpoint as 137 Cs gamma rays. A simple conversion factor for equating x-ray effects to 137 Cs effects was not recommended because relative biological effectiveness depends on multiple factors. They concluded that each experiment should be individually calibrated when converting from 137 Cs irradiators to x-ray irradiators. The lessons learned from implementing the project to date have shown the importance of having senior management buy-in, involving the research community in the decision making process and allowing for exceptions where equivalency of 137 Cs to x ray cannot be established.